2010
DOI: 10.1139/w10-073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbon source on growth and mycotoxin production by isolates of Pyrenophora tritici-repentis from wheat

Abstract: The fungus Pyrenophora tritici-repentis can infect wheat kernels, causing red smudge, and has been shown to produce the anthraquinone mycotoxins emodin, catenarin, and islandicin. The growth of 8 fungal isolates from diverse regions was evaluated on various culture media and was found to be generally slowest on the semisynthetic Fries medium. The choice of carbon source had a significant effect on mycotoxin production, as assessed by high-performance liquid chromatography. The highest emodin concentration (194… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…(Table S16). Ptr is known to produce anthraquinone-derived phytotoxins (Bouras and Strelkov, 2010; Bouras et al 2009) and a biosynthetic cluster similar to the emodin cluster of Aspergillus nidulans (Bok et al 2009) was identified in the reference genome. Also found are clusters related to those in other fungi that produce resorcyclic-lactone-based compounds [ i.e.…”
Section: Resultsmentioning
confidence: 99%
“…(Table S16). Ptr is known to produce anthraquinone-derived phytotoxins (Bouras and Strelkov, 2010; Bouras et al 2009) and a biosynthetic cluster similar to the emodin cluster of Aspergillus nidulans (Bok et al 2009) was identified in the reference genome. Also found are clusters related to those in other fungi that produce resorcyclic-lactone-based compounds [ i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the chromatograms for these 10 different cultivation media (Figure 1) clearly depicted a dramatic change in the chemical profiles. Cultivation on yeast extract glucose (GYE), 12 soya flour mannitol (SFM), 13 and potato dextrose (PD) 14 media resulted in the production of a sole metabolite, chaxamycin A (7), which was also found as a predominant metabolite in all of the other media used. As a result, the previously reported chaxamycin A (7) 6 is considered a useful chemical marker of this strain.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…While the case for such changes in morphology is unknown, it is possible that the reddish pigmentation observed in the colonies may be responsible for the red smudge symptoms, if in high abundance under the right conditions. Ptr is known to produce several mycotoxins from the anthraquinone class such as emodin, islandicin and catenarin [24][25][26], and both catenarin and emodin have been detected in Ptr-infected grain. Catenarin has been hypothesized to cause red smudge due to the red pigmentation property of the compound [27].…”
Section: Discussionmentioning
confidence: 99%